Análise da terceirização na engenharia de segurança do trabalho: suas influências e impactos para as empresas - Claudino, Clóvis Reis (My University, 2021)
This work presents its motivation based on the scenario generated by Law No. 13,429 / 17 that allowed unrestricted outsourcing, contributing to the provision of services by the professional work safety engineer (EST), in companies. The objective is to know and analyze the main visions and perceptions of companies regarding the outsourcing of this type of professional service. Three categories of analysis were defined which are: to identify the main reasons that lead companies to outsource; the main services that are necessary in this search for outsourcing; and the interference, efficiency and impacts that these services provide to these companies. The work was conducted by means of a quantitative research, type survey, applied in 104 respondent companies in the region of Caxias do Sul of the state of Rio Grande do Sul. The work addressed the three categories of analysis and defined 10 hypotheses of which 7 were confirmed. The results showed that companies with 11 to 50 employees are the ones that most perform this type of outsourcing and even those companies that already have EST, as an employee, still hire services from other EST professionals on an outsourced basis. Most of the contracted services are linked to reports and risk assessment programs. It could be observed that companies are concerned with keeping their work environments adequate to safety standards to avoid problems related to illnesses and accidents at work, as well as labor liabilities, fines or stoppage of their activities, but more than half of the companies surveyed reported that the main reason that hinders the fulfillment of work safety standards are the costs of adapting the standards themselves. Companies realize the need and importance of the services developed by EST's with more experience, well trained and equipped so that their service provision is effective and brings safe solutions to their ventures.Finally, it is concluded that future work may be carried out in order to cover the research to other regions and with even greater numbers of samples to verify whether cultures from different regions interfere with the results obtained [resumo fornecido pelo autor].
Este trabalho apresenta sua motivação baseado no cenário gerado pela Lei n° 13.429/17 que permitiu a irrestrita terceirização, contribuindo para prestação de serviços do profissional engenheiro de segurança do trabalho (EST), nas empresas. O objetivo é conhecer e analisar as principais visões e percepções das empresas quanto a terceirização desse tipo de serviço profissional. Foram definidas três categorias de análise que são: identificar os principais motivos que levam as empresas a terceirizar; os principais serviços que se fazem necessário nesta busca pela terceirização; e a interferência, eficiência e impactos que estes serviços prestados causam a estas empresas. O trabalho foi conduzido por meio de uma pesquisa quantitativa, tipo survey, aplicada em 104 empresas respondentes da região de Caxias do Sul do estado do Rio Grande do Sul. O trabalho abordou as três categorias de análises e definiu 10 hipóteses das quais 7 foram confirmadas. Os resultados mostraram que as empresas de 11 a 50 empregados são as que mais realizam este tipo de terceirização e mesmo aquelas empresas que já possuem o EST, como empregado, ainda assim contratam serviços de outros profissionais EST de forma terceirizada. Na sua grande maioria os serviços contratados estão ligados a laudos e programas de avaliações de riscos. Pôde ser observado que as empresas se preocupam em manter seus ambientes de trabalho adequados as normas de segurança para evitar problemas relacionados a doenças e acidentes de trabalho, bem como passivos trabalhistas, multas ou paralizações de suas atividades, mas mais da metade das empresas pesquisadas relataram que o principal motivo que dificulta o cumprimento das normas de segurança do trabalho são os custos em adequações as próprias normas. As empresas percebem à necessidade e importância dos serviços desenvolvidos pelos EST com maior experiência, bem capacitados e aparelhados para que sua prestação de serviço seja efetiva e traga soluções seguras para seus empreendimentos. Por fim, conclui-se que futuros trabalhos poderão ser realizados visando abranger a pesquisa para outras regiões e com número até maiores de amostras para verificar se as culturas de diferentes regiões interferem nos resultados obtidos [resumo fornecido pelo autor].
Keywords: Terceirização; Segurança do trabalho; Contracting out; Industrial safety